Development, validity and reliability testing of the East Midlands Evaluation Tool (EMET) for measuring impacts on trainees’ confidence and competence following end of life care training - Whittaker, B.; Parry, R.; Bird, L.; Watson, S.; Faull, Christina (BMJ Publishing Group, 2017)
Objectives: To develop, test and validate a versatile questionnaire, the East Midlands Evaluation Tool (EMET), for measuring effects of end of life care training events on trainees’ self-reported confidence and competence.